Using lake sediment cores to improve records of volcanism at Aluto volcano in the main Ethiopian rift - McNamara, K; Cashman, K; Rust, A; Fontijn, K; Chalié, F; Tomlinson, E; Yirgu, G (American Geophysical Union, 2018)
Aluto is a silicic volcano in central Ethiopia, flanked by two large population centers and home to an expanding geothermal power plant. Here we present data from two lake sediment cores sampled 12 km and 25 km from the volcano, which record at least 24 distinct eruptions in the Holocene. Tephra layers from the two cores are correlated using a variety of techniques, including major and trace element geochemistry as well as textural and morphological features from SEM‐BSE imaging. The purpose is to provide a Holocene reference section for further tephrostratigraphic studies of the volcano as well as to provide information on eruption frequency. The lake cores suggest that Aluto has had a variable eruption rate, with three eruption ‘clusters' in the Holocene at ~3, 6.5 and 11 ka, with small Vulcanian‐to sub‐Plinian eruptions separated by larger, Plinian eruptions. We infer that the smaller tephras are likely the product of pumice cone‐ and dome‐ forming eruptions. In addition, modern wind data suggest the likely direction of an ash cloud from Aluto is to the west and south west, which is towards population centres and is in agreement with thickness data from the cores. We conclude that current records underestimate the volcano's eruptive history and that hazard assessments should be updated accordingly.